Review paperThe use of drug-eluting stents in acute myocardial infarction – is the battle coming to an end? From despair to acceptance - Kübler, Piotr; Reczuch, Krzysztof (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
The large-scale use of drug-eluting stents (DES) in elective percutaneous coronary interventions resulted in a significant reduction of restenosis and the need for repeat revascularization, compared to bare-metal stents (BMS) and balloon angioplasty. The position of DES used during primary percutaneous coronary intervention was not so well established. Based on the trials including the general population of patients, an increased risk of stent thrombosis was indicated, particularly late after implantation, which may be associated with increased mortality. A number of randomized clinical trials have compared first generation DES with BMS in acute ST-segment elevation myocardial infarction (STEMI). In most of them increased mortality after DES implantation was not confirmed, with demonstrated reduction of repeat revascularizations. However, long-term follow-up of these studies and the results from non-randomized “real world” registries are equivocal. A new generation of DES has been present on the market for several years. They have modern designs, are covered with more neutral polymers and release new drugs. The new generation DES have a better safety and efficacy profile, including a population of patients with acute STEMI, than the first generation stents. This paper is a review of randomized controlled trials, meta-analyses and registries, comparing DES with BMS in patients with acute STEMI. Attention was drawn to the current position and the role of new generation DES, which may prove to be a safe and effective choice in this population of patients.